Note on Strobilanthes sanjappae (Acanthaceae) - Santhosh Kumar, Ettickal Sukumaran; Rajvikraman, Ramachandrakurup; Prakashkumar, Raveendran Pillai (Phytotaxa, 2020)
The plieteial genus Strobilanthes Blume (1826: 781) is the second largest genus in the family Acanthaceae. It consists of about 465 species widely distributed in tropical and subtropical regions of South and South East Asia (Mabberley 2017; Jomy 2018). About 150 species have been reported from India, of these 62 are reported from South India (Carine & Scotland 2002, Venu 2006).